SIRKUMSISI PADA ANAK DI KELURAHAN AGROWISATA KECAMATAN RUMBAI PEKANBARU - Mursyida, Eliya (Jurnal Pengabdian Masyarakat Multidisiplin, 2019)
Circumcision is a medical action that is beneficial to the interests of religion and health. One of the factors that causes parents not to encourage their children to do circumcision is economic problems. The results of this activity took the form of circumcision of orphans and the underprivileged by 17 children. The number of participants circulated by 17 children came from various RWs located in the Agrowisata Village. There were 7 respondents aged 11 years, 5 respondents aged 9 years, 3 respondents were 10 years old, and 1 respondent was 8 years old. No abnormalities of the penis were found during history taking and physical examination.